Aquaponics Food Production Systems Combined Aquaculture and Hydroponic Production Technologies for the Future - Goddek, Simon; Joyce, Alyssa; Kotzen, Benz; Burnell, Gavin M. (Springer Nature, 2019)
This open access book, written by world experts in aquaponics and related technologies, provides the authoritative and comprehensive overview of the key aquaculture and hydroponic and other integrated systems, socio-economic and environmental aspects. Aquaponic systems, which combine aquaculture and vegetable food production offer alternative technology solutions for a world that is increasingly under stress through population growth, urbanisation, water shortages, land and soil degradation, environmental pollution, world hunger and climate change.